Analisis Strategi Distribusi Zakat dalam Bidang Pendidikan dan Kewirausahaan di Lazismu Kota Medan - Fauzi Irsyad; Nurlaila; Muhammad Lathief Ilhamy Nasution (Universitas Muhammadiyah Surabaya, 2024)
Abstract This research aims to investigate the zakat distribution strategies in the fields of education and entrepreneurship at LAZISMU (Lembaga Amil Zakat, Infaq, dan Sadaqah Muhammadiyah) in Medan City, along with the obstacles encountered. The data analysis technique employed in this study is descriptive qualitative analysis using the Miles and Huberman analysis model. The primary data collection techniques and instruments consist of structured interviews, supplemented by secondary data sources such as financial reports, books, journals, and others. The findings reveal that LAZISMU in Medan City does not implement specific strategies for zakat distribution. Thus, it can be concluded that LAZISMU distributes zakat using similar strategies as other LAZs (Lembaga Amil Zakat) or BAZs (Badan Amil Zakat) focusing on efficient financial management and human resource management strategies. The obstacles encountered in zakat distribution in the fields of education and entrepreneurship at LAZISMU in Medan City generally fall into two clusters: (1) internal cluster with obstacles related to human resources and governance aspects, and (2) external cluster with obstacles related to location and mustahik (zakat recipients) decision-making aspects.